A new species of freshwater crab of the genus Badistemon Yeo & Ng, 2007 (Decapoda: Brachyura: Potamidae: Potamiscinae) from Manipur State, India, with the reassignment of Potamiscus pealianus (Wood-mason, 1871) - Mitra, Santanu; Monica, Thingbaijiam; Waikhom, Mema Devi (Zootaxa, 2020)
A new species of potamid crab of the genus Badistemon Yeo & Ng, 2007, is described from Kamjong district of Manipur, India. Badistemon fulvum n. sp., can be distinguished from congeners by a distinct combination of carapace and gonopod characters: carapace subquadrate, convex, dorsal surface glabrous, cervical groove superficial, anterolateral margin longer than posterolateral margin; cornea relatively large; sixth male pleonal somite trapezoidal in shape, male telson broader than long; terminal segment of male first gonopod relatively long, outwardly bent, sub cylindrical with low and short dorsal flap, tip pointed, groove for male second gonopod terminal. Holotype and paratypes of Potamiscus pealianus (Wood-mason, 1871) are re-examined, and the species is here referred to Badistemon as carapace morphology and male gonopods characters are found congeneric with the genus. A key for all the three species of Badistemon are provided.